The effects of prebiotics on faecal microbiota in critical care patients receiving enteral nutrition / Mazuin Kamarul Zaman - Mazuin, Kamarul Zaman (2016)
The provision of nutrition through enteral nutrition (EN) helps to maintain gut function. However, despite the importance of EN to patients, diarrhoea is a common complication in those receiving EN. Meta-analysis conducted revealed that fibre supplementation in enteral formula reduces diarrhoea incidence in patients receiving EN. However, the positive effect was only seen in non-critically ill patients. The undigested fibre (prebiotics) will be fermented to short chain fatty acid (SCFA) and stimulate the growth of bifidobacteria which helps in minimising diarrhoea. In the current literature, the effect of fibre and prebiotics supplementation on faecal microbiota and SCFA remain disputable. The aim of this study is to evaluate faecal microbiota concentrations (total bacteria, bifidobacteria, lactobacilli, bacteroides, clostridia and Faecalibacterium prausnitzii) and the incidence of diarrhoea between critically ill patients who receive enteral formula with and without fibre/prebiotics during EN. Randomised Controlled Trial (RCT) was conducted on critically ill, adult patients receiving EN as clinically indicated. Patients were randomly allocated to receive EN with fibre-free or fibre/prebiotics-supplemented enteral formula for up to 14 days. Nutritional delivery and diarrhoea scores were recorded daily. Faecal samples were collected at baseline, 1 week and 2 weeks and analysed for the quantification of microbiota using the real time polymerase chain reaction. Of 702 critically ill patients screened, 68 patients were recruited into the study (35 in the fibre/prebiotics group and 33 in fibre-free group). These two groups of patients were similar in demographics, disease severity, number of antibiotics used, nutritional status and nutritional intake at baseline. The results of the RCT revealed that the provision of 10 g/L of prebiotics containing enteral formula to critically ill patients were not able to increase the faecal bifidobacteria concentration (PP: p= 0.537, ITT: p= 0.974). However, the findings from this study showed that patients in the fibre/prebiotics group had improvements in their faecal outputs as evidence by a trend of lower stool frequency (1.2±0.6) compared to patients receiving the fibre-free enteral formula (1.8±0.9), (PP: p= 0.092, ITT: p= 0.070). However, there were no significant differences in the faecal scores between patients in the fibre/prebiotics group and the fibre-free group (PP: p= 0.613, ITT: p= 0.036). These data support the view that the provision of prebiotics as the sole source of fibre containing enteral formula may not increase the faecal bifidobacteria concentrations of critically ill patients requiring EN. However, the provision of prebiotics may be useful in alleviating diarrhoea by reducing the stool frequency. It is hoped that the findings from this research will be of use to health care professionals in managing the common complication of EN in this group of patients.